Analisis Fitokimia Umbi Talas Jepang Colocasia esculentai L. (Schott) var. antiquorum dan Talas Kimpul Xanthosoma sagittifolium L. (Schott) dari Dataran Rendah - A Masniawati; Eva Johannes; Winda Winarti (Universitas Hasanuddin, 2021)
This research aims to determine the phytochemical compounds of the Japanese taro tuber Colocasia esculenta L. (Schott) var. antiqourum and local taro tubers Kimpul Xanthosoma sagittifolium L. (Schott). This research was conducted in June-August 2020 at the Pharmacy Laboratory, Faculty of Pharmacy, Hasanuddin University, Makassar. This research was carried out from sample preparation, extraction, identification with Mayer, and Dragendroff's reagent, then identified by Thin Layer Chromatography (TLC). Data analysis is presented descriptively by looking at changes in color and shape of the tested liquid. The results of this research indicate that the extract of the Japanese taro tuber Colocasia esculenta L. (Schott) var. antiqourum and local taro tubers Kimpul Xanthosoma sagittifolium contains bioactive alkaloids, flavonoids, steroids / triterpenoids, tannins and saponins.